Review on Exercise Regulation of Autophagy in Reducing Myocardial Ischemia Reperfusion Injury - Xue WANG; Luwen ZHU; Hongyu LI; Yuhong CHEN; Qiang TANG (康复学报)
Early recovery of myocardial perfusion after acute myocardial infarction is the most effective method to reduce the area of myocardial infarction and improve the clinical prognosis. However, hemodynamic reperfusion after myocardial ischemia may cause myocardial reperfusion injury.This study reviews the relationship between autophagy and related signaling pathways; autophagy which as a self-protective mechanism plays a dual role in the stage of myocardial ischemia and reperfusion;appropriate intensity of exercise training can regulate the level of autophagy of myocardial cells, so as to protect cardiac function and reduce myocardial ischemia-reperfusion injury.